Sustainability and AI in Automotive E-Commerce: Analyzing Eco-Friendly Consumer Choices - Vijaya Kumar Reddy Atla (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Artificial intelligence and sustainability concerns are coming together to change the automotive e-commerce industry completely and how buyers approach car purchases. This article thoroughly investigates how intelligent systems support and encourage environmentally conscious purchasing decisions, examining the complex interactions between AI technology and eco-conscious customer behavior in the car industry. This article illustrates how AI-driven platforms are changing the automobile retail scene while encouraging sustainable choices by examining personalized recommendation systems, predictive analytics, and environmental impact assessments. The article emphasizes how important cutting-edge technologies are to improve supply chain transparency, charging infrastructure optimization, and customer awareness of environmental effects—all of which lead to a more sustainable car sector.